PENGARUH CAR, NPL, KOMITE AUDIT, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP PROFITABILITAS BANK UMUM KONVENSIONAL GO PUBLIC PERIODE 2015 – 2017 - Rini Indarti; Minanari Minanari (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2019)
This research aims to examine the influence of Capital Adequacy Ratio, Non Performing Loan, Audit Committee and Institutional Ownership on Profitability (Empirical Studies on Conventional Commercial Banks Registered on the Indonesia Stock Exchange for the Period of 2015 – 2017). The sample in this research were 99 of 33 Conventional Commercial Banks criteria sampliing. The sampling technique used in the research was purposive sampling method. This research uses a statistical analysis model in the form of multiple regression tests. The results of this research indicate that Capital Adequacy Ratio has a significant positive effect on Return on Assets, Non Performing Loan has a significant negative effect on Return on Assets, Audit Committee and Institutional Ownership have no effect on Return on Assets.